Cultural Politics of Love and Provision among Poor Youth in Urban Tanzania. Issue 3 (27th May 2017) - Stark, Laura
ABSTRACT: This article examines how urban youth in the poorest neighbourhoods of Dar es Salaam negotiate the terms of transactional intimacy, that is, heterosexual relations in which men are expected to provide for women materially. Using the concept of 'affect', I argue that this negotiation involves different levels of male providership, as well as moral values attached to notions of 'true love' and the Swahili concept of tamaa. Poor men and women view their agency differently within transactional intimacy, with women describing themselves as exploited by men who do not fulfil their end of the transactional bargain, and poor men portraying themselves as deeply disempowered in comparison to wealthier men. Yet women and men also produce shared cultural discourses to portray men's meagre providership in a positive light, and to place upon women the moral onus of sacrificing material aspirations in order to choose 'true love'.